2017
DOI: 10.4236/ojpm.2017.75008
|View full text |Cite
|
Sign up to set email alerts
|

Effect That Lifestyle during the Growth Period Has on Bone Density Acquisition—Using Simple Exercise and a Nutrition Survey

Abstract: This survey was conducted with the aim of clarifying and providing guidance regarding correct lifestyle and exercise habits from adolescence in order to prevent the development of osteoporosis. The subjects included 195 Japanese adult females. We measured their calcaneal bone density by ultrasonography, the index of which was determined as SOS (Speed of Sound). We examined their physical characteristics, health conditions, amount of physical activity, exercise history, and eating habits, and then analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There are reports suggesting that there is no relationship between nutrients and SOS [8] [9]. In a longitudinal study using the DXA method (dual-energy X-ray absorptiometry) for 15 years from the age of 13 to 28, body weight change, rather than calcium intake, during the observation period, indicated a stronger relation to bone mass change [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports suggesting that there is no relationship between nutrients and SOS [8] [9]. In a longitudinal study using the DXA method (dual-energy X-ray absorptiometry) for 15 years from the age of 13 to 28, body weight change, rather than calcium intake, during the observation period, indicated a stronger relation to bone mass change [8].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a report indicating that a study using quantitative ultrasound measurement methods to compare changes in indices, including when skipping meals, excess consumption of instant foods, smoking and drinking behavior, etc., which seem to reflect lifestyle disturbances, found no association and only finding a statistically significant difference in the item "exercise habits." [9]. Furthermore, it has been suggested that the intake frequency of dairy products, such as milk and cheese, is strongly related to changes in bone mass [10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, more than half of the students had dieting experience, with 31% of those in the normal weight group and 21% of those in the underweight group currently on a diet. In other words, we found a tendency for the number of students with dieting experience to increase as the BMI value rises [9] [10]. However, there is a concern regarding being extremely underweight since the percentage of students in the underweight group with dieting experience reached up to 31%.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects consisted of 124 female college students. A sufficient number of subjects and average female college students were sorted out from this study in line with other similar studies [9] [10]. Their average age was 21.4.…”
Section: Methodsmentioning
confidence: 99%